2021
DOI: 10.1016/j.wroa.2020.100085
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced hydraulic cleanability of biofilms developed under a low phosphorus concentration in reverse osmosis membrane systems

Abstract: A critical problem in seawater reverse osmosis (RO) filtration processes is biofilm accumulation, which reduces system performance and increases energy requirements. As a result, membrane systems need to be periodically cleaned by combining chemical and physical protocols. Nutrient limitation in the feed water is a strategy to control biofilm formation, lengthening stable membrane system performance. However, the cleanability of biofilms developed under various feed water nutrient conditions is not well unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 63 publications
2
12
0
Order By: Relevance
“…They are natural amphiphilic polymers that aid in bacterial detachment from interfaces ( Neu and Lawrence 2010 ). Recently, it was reported that the higher presence of fulvic acids in the biofilm grown at a lower phosphorus concentration helped solubilize and detach the biofilm from the membrane and spacer ( Javier et al. 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are natural amphiphilic polymers that aid in bacterial detachment from interfaces ( Neu and Lawrence 2010 ). Recently, it was reported that the higher presence of fulvic acids in the biofilm grown at a lower phosphorus concentration helped solubilize and detach the biofilm from the membrane and spacer ( Javier et al. 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…For efficient biofouling control, it may be suggested to (i) understand the site-specific processes influencing biofilm formation, (ii) implement preventive control strategies such as effective pretreatment to delay biofouling and (iii) examine biofouling characteristics to select the most effective membrane cleaning method. It is known that biofilm EPS composition can vary with age, nutrient availability in feed water and membrane surface properties ( Javier et al. 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dechlorinated tap water supplemented with nutrients (Table 1), containing an ultralow phosphorus concentration of ≤0.3 µg PO 4 -P•L −1 measured as orthophosphate according to Javier et al (2020Javier et al ( , 2021 [9,31,33], was used as the feed water for this study. The tap water was produced through seawater reverse osmosis (SWRO) desalination at the King Abdullah University of Science and Technology desalination plant (Thuwal, Jeddah, Saudi Arabia).…”
Section: Experimental Setup and Operational Parameters During Biofilm...mentioning
confidence: 99%
“…The 125 µg C•L −1 assimilable organic carbon concentration of glucose was used based on measurements performed at a desalination plant [42]. The dosed phosphorus concentrations for this study, 3 µg P•L −1 and 6 µg P•L −1 , were selected based on phosphorus measurements that are typically present in seawater and the RO feed water after the addition of phosphorus-based antiscalants [31,43]. The selected dosed phosphorus concentration of 0 µg P•L −1 was used as removing the phosphorus concentration from the feed water has been suggested as a biofilm control strategy [12,44].…”
Section: Forward Flushing and End Of The Experimentsmentioning
confidence: 99%
See 1 more Smart Citation